Effects of an amino acid/creatine energy supplement on the acute hormonal response to resistance exercise - Ratamess, N. A.; Hoffman, J. R.; Ross, R.; Shanklin, M.; Faigenbaum, A. D.; Kang, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
The authors aimed to examine the acute hormonal and performance responses to resistance exercise with and without prior consumption of an amino acid/creatine/energy supplement. Eight men performed a resistance-exercise protocol at baseline (BL), 20 min after consuming a supplement (S) consisting of essential amino acids, creatine, taurine, caffeine, and glucuronolactone or a maltodextrin placebo (P). Venous blood samples were obtained before and immediately after (IP), 15 min (15P), and 30 min (30P) after each protocol. Area under the curve of resistance-exercise volume revealed that BL was significantly less than S (10%) and P (8.6%). For fatigue rate, only S (18.4% ± 12.0%) was significantly lower than BL (32.9% ± 8.4%). Total testosterone (TT) and growth hormone (GH) were significantly elevated at IP and 15P in all conditions. The GH response was significantly lower, however, in S and P than in BL. The TT and GH responses did not differ between S and P. These results indicated that a supplement consisting of amino acids, creatine, taurine, caffeine, and glucuronolactone can modestly improve high-intensity endurance; however, the anabolic-hormonal response was not augmented.